(untitled) (Research, Society and Development, 2021)
Federal Decree n. 7397, of December 22, 2010, formalized the basic guidelines for financial education in Brazil. Based on the established guidelines, projects on financial education were created in order to make public policy on the subject in Brazil feasible. Thus, the purpose of this article is to reflect on financial education as a public policy in Brazil, analyzing whether the existence of projects that meet the basic guidelines of financial education promote awareness for optimizing the budget of Brazilian families. Through research results published on official websites of the Brazilian federal government and in scientific journals that address the subject, a qualitative theoretical research was carried out. The results show that although there is a need for financial education to be treated as a public policy, the projects arising from the guidelines provided for in the legislation are not capable of promoting, by themselves, direct changes in individual behavior with regard to care for the family budget.